Youth Volunteers Of Anti-Drug Program: Initial Assessment In Kuala Terengganu, Terengganu, Malaysia - Abdul Ghani, Norizan; Mohamad, Abdul Manam; -, Dara Aisyah; Ibrahim, M. (2013)
Youth volunteers of Anti-Drug Program is a public program that aims to provide technical knowledge and awareness pertaining to drug addictions, ensure drug-free families, help organizations to mobilize efforts for a drug-free workplace and drug-free community. This study seeks to find out the possible problems pertaining to this voluntary program as youth in Kuala Terengganu, Malaysia were found to be the target group. This study aims to identify the factors that cause the problems faced by the volunteers in this program. A total of 245 volunteers were involved in this Youth Anti-Drug Voluntary Program, based in Kuala Terengganu, Malaysia. This study is a descriptive study, using questionnaire as an instrument in the data collection procedure, which consists of three sections including respondents’ background, factors that cause members to be involved with the program and ways to overcome problems in this voluntary youth program. Data were analyzed using the Statistical Packages for the Social Science (SPSS) software, and is discussed in terms of percentages, frequencies and mean. The findings show that participants’ lack of participation, no post-mortem meetings between members of the organization, lack of systematic management skills as well as no diversity of activities are among the factors that cause such problems in making this Youth Anti-Drug Voluntary Program a success. Most participants agreed that factors like education, experience, passion, and talent can be listed as a few of the key factors in the success of the program. It was also recommend that meeting with new people, visits, social service, programs with drug addicts should be held and organized in order to make this voluntary program a success. Besides that, the main factors required of participants in this program are spiritual awareness through education, motivational camps, as well as outdoor anti-drug camps like camping, and cooperative work.